Biomechanical modeling of laryngeal dynamics - Döllinger, Michael; Yang, Anxiong; Stingl, Michael; Eysholdt, Ulrich; Lohscheller, Jörg (2008 First International Symposium on Applied Sciences on Biomedical and Communication Technologies, 2008)
Interferences in the laryngeal area based on anatomical alterations or disturbances being only visible during vocal fold oscillations yield hoarseness. Most often, asymmetries caused by the vibrating vocal folds are the origin for this hoarseness. This work presents an enhancement of biomechanical models to simulate three dimensional vocal fold vibrations. The model consists of coupled mass-spring elements similar to Ishizaka and Flanagan (1972). The new model simulates the vibrations at 25 different positions for each vocal fold. The masses are arranged at 5 positions in longitudinal direction by 5 positions in vertical direction. The masses are capable to move in all three physical directions to better simulate human laryngeal vocal fold vibrations. The physical parameters applied in the model were chosen to visually fit real three-dimensional excised human vocal fold dynamics. Exemplarily, a symmetric dynamics simulation will be given.

Computation of physiological human vocal fold parameters by mathematical optimization of a biomechanical model. - Yang, Anxiong; Stingl, Michael; Berry, David A.; Lohscheller, Jörg; Voigt, Daniel; Eysholdt, Ulrich; Döllinger, Michael (Journal of the Acoustical Society of America, 2011)
With the use of an endoscopic, high-speed camera, vocal fold dynamics may be observed clinically during phonation. However, observation and subjective judgment alone may be insufficient for clinical diagnosis and documentation of improved vocal function, especially when the laryngeal disease lacks any clear morphological presentation. In this study, biomechanical parameters of the vocal folds are computed by adjusting the corresponding parameters of a three-dimensional model until the dynamics of both systems are similar. First, a mathematical optimization method is presented. Next, model parameters (such as pressure, tension and masses) are adjusted to reproduce vocal fold dynamics, and the deduced parameters are physiologically interpreted. Various combinations of global and local optimization techniques are attempted. Evaluation of the optimization procedure is performed using 50 synthetically generated data sets. The results show sufficient reliability, including 0.07 normalized error, 96% correlation, and 91% accuracy. The technique is also demonstrated on data from human hemilarynx experiments, in which a low normalized error (0.16) and high correlation (84%) values were achieved. In the future, this technique may be applied to clinical high-speed images, yielding objective measures with which to document improved vocal function of patients with voice disorders.

Intelligibility of laryngectomees' substitute speech: automatic speech recognition and subjective rating - Schuster, Maria; Haderlein, Tino; Nöth, Elmar; Lohscheller, Jörg; Eysholdt, Ulrich; Rosanowski, Frank (European Archives of Oto-Rhino-Laryngology, 2006)

Registration of PE segment contour deformations in digital high-speed videos - Stiglmayr, Michael; Schwarz, Raphael; Klamroth, Kathrin; Leugering, Günter; Lohscheller, Jörg (Medical Image Analysis, 2008)
We present an algorithm that automatically registers one segmented contour in a frame of the video sequence to the contour in the next frame to derive discrete 2-D trajectories of PE vibrations. By concatenation of the obtained transformations this approach provides a total registration of PE segment contours. We suggest a mixed-integer programming formulation for the problem that combines an advanced outlier and deformation handling with the introduction of dummy points in regions that newly open up, and that includes normal information in the objective function to avoid unwanted deformations. Numerical experiments show that the implemented alternate convex search algorithm produces robust results which is demonstrated at the example of five high-speed recordings of laryngectomee subjects. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: substitute voice; PE segment; digital high-speed videos; point matching; shape registration; generalized assignment problem; 2-D trajectories